Aplikasi Pembelajaran Berbasis Multimedia Di SDIT Al- Kautsar Cikarang Dengan Metode MDLC - Nuraini Purwandari; Jullend Gatc (Universitas Pancasila, 2020)
SDIT Al-Kautsar is an Integrated Islamic Elementary School located in Cikarang that has not yet implemented the teaching and learning process using information technology. The obstacle faced is the lack of creativity of teachers in applying models or learning strategies to students, especially on thematic subjects. In the world of education, especially schools, one of the interesting and creative learning media is multimedia. However, with technological advances, this can be done with the help of props or projectors. This study aims to create multimedia applications as learning media, especially thematic subjects for students and improve teacher competence in the use of teaching media. This study uses Multimedia Development Life Cycle (MDLC) method. The results of this study are multimedia-based applications that can produce output in the form of images, animations and videos about thematic material at the Integrated Islamic Elementary School (SDIT) Al-Kautsar.